On the Impact of Taobao's Big Data Push on Teenage Users' Consumption Behavior - Chen, Xinyu (International Journal of Global Economics and Management, 2024)
With the rapid development of Internet technology in recent years, the technology of big data has become more and more widespread in the application of e-commerce. Besides, with the widespread popularity of smartphones, consumers are able to access e-commerce platforms anytime and anywhere, which also generates a large volume of user data and transaction behaviour information. In China, Taobao, as one of the largest e-commerce platforms in the country, has made use of artificial intelligence (AI) and machine learning (ML) technology to allow the platform to accurately profile users, personalised recommendations and other functions. The youth group, as an important part of the market consumer group, has a strong desire to buy. And their behavioural characteristics in online shopping are unique, which also includes their attention to various interactive software pushes when using mobile phones. This paper investigates the impact of Taobao's big data push on the consumption behaviour of teenage users. The study finds that Taobao's big data push significantly impacts teenage consumers' behavior.